2020
DOI: 10.1037/abn0000501
|View full text |Cite
|
Sign up to set email alerts
|

Moral incongruence and compulsive sexual behavior: Results from cross-sectional interactions and parallel growth curve analyses.

Abstract: Despite controversies about the diagnosis, the World Health Organization recently elected to include compulsive sexual behavior disorder in the 11th edition of the International Classification of Diseases. Both recent and remote works have suggested that various cultural factors such as personal religiousness and morality can influence both the experience and expression of compulsive sexual behaviors. Because prior works have indicated that pornography use is likely to be the most common expression of compulsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 48 publications
2
46
1
Order By: Relevance
“…However, there is also an additional issue here: these kinds of statements do not accurately appraise moral incongruence, but rather moral disapproval. 37 This remark is consistent with some of the earlier works led by Grubbs et al, 36,38 in which the label "moral disapproval" was used. The reason is 2 fold: (i) the variable lacks the component of awareness or sensitivity to one's own behavior transgressing believed norms (refer to the study by Wright 22 ) and (ii) most studies on the relationship between moral incongruence and self-perceived addiction are based on subjects who declare a lifetime exposure to pornography-this is also the case for the present study.…”
Section: Moral Incongruence Vs Moral Disapproval In the Ppmi Model Ansupporting
confidence: 86%
See 1 more Smart Citation
“…However, there is also an additional issue here: these kinds of statements do not accurately appraise moral incongruence, but rather moral disapproval. 37 This remark is consistent with some of the earlier works led by Grubbs et al, 36,38 in which the label "moral disapproval" was used. The reason is 2 fold: (i) the variable lacks the component of awareness or sensitivity to one's own behavior transgressing believed norms (refer to the study by Wright 22 ) and (ii) most studies on the relationship between moral incongruence and self-perceived addiction are based on subjects who declare a lifetime exposure to pornography-this is also the case for the present study.…”
Section: Moral Incongruence Vs Moral Disapproval In the Ppmi Model Ansupporting
confidence: 86%
“…It is possible that subjects who use pornography rarely (eg, once or twice a year, or even with greater frequency) and see pornography use as to some degree morally wrong still do not experience feelings of incongruence because occasional transgressions can be easily ignored. In the most recent work, Grubbs et al 37 operationalize moral incongruence as the interaction between moral disapproval and pornography use, which is a significant improvement. However, it addresses the second point delineated previously, but not the first one, as this method of measurement still does not reflect the component of awareness or sensitivity to misalignment between one's own behavior and norms.…”
Section: Moral Incongruence Vs Moral Disapproval In the Ppmi Model Anmentioning
confidence: 99%
“…Importantly, moral incongruence is one of the most robust and consistent predictors of self-reported addiction to pornography. These findings are clear in cross-sectional, nationally representative U.S. samples and longitudinally over a 1-year time period (Grubbs, Kraus, et al, 2020). In short, there is evidence that religiously based moral disapproval of pornography is uniquely predictive of self-reports of addiction to pornography, suggesting that moral incongruence might obfuscate some aspects of the diagnostic process for CSBD.…”
Section: Clinical Concerns About Pornographymentioning
confidence: 94%
“…Additionally, in the current article the term 'moral incongruence' is used for consistency with the work of Grubbs et al [34]. However, recently it has been suggested that the measured construct may be better termed 'moral disapproval', and new ways of measuring 'moral incongruence' that may arise from 'moral disapproval' warrant consideration and testing in future research [71,75]. Last, when operationalizing variables, we followed work by Grubbs et al 2019 [34] and used short measures, including the precise one-item indicator of moral incongruence (see discussion on measuring moral incongruence [71]).…”
Section: Limitationsmentioning
confidence: 96%